Description of two calls of Eleutherodactylus rubrimaculatus (Anura: Eleutherodactylidae) in Chiapas, Mexico - Mendoza-Henao, Angela M.; Hernández-Austria, Raquel; López-Velázquez, Aldo; Parra-Olea, Gabriela (Zootaxa, 2020)
Frogs of the genus Eleutherodactylus are direct developing frogs grouped into five subgenera and 192 species, with a geographic distribution primarily centered in the Caribbean (Padial et al. 2014). Eleutherodactylus species inhabit a variety of environments such as tropical and temperate forests, and scrub, where they occupy different microhabitats including caves, floors rich in leaf litter, cracks and cavities of limestone and volcanic outcrops (Reyes-Velasco et al. 2015). Mexico harbors 33 species of Eleutherodactylus (AmphibiaWeb 2018), most of them distributed in central-western and southwestern Mexico (Reyes-Velasco et al. 2015).